Peran Psychological Empowerment dalam Memediasi Pengaruh Workplace Spirituality terhadap Change Oriented-Organizational Citizenship Behavior - Apriliana, Kartika; Amin, Shofia; Wediawati, Besse (Universitas Batanghari Jambi, 2025)
This study was conducted at the Regional Human Resources and Development Agency (BKPSDM) of Tanjung Jabung Barat Regency and aims to examine the role of workplace spirituality (WS) on change-oriented organizational citizenship behavior (OCB-CH), mediated by psychological empowerment (PE). This is a quantitative study, with the population comprising all 91 employees of BKPSDM Tanjung Jabung Barat Regency. The sampling method used in this research is total sampling. Data analysis was carried out using the Structural Equation Modeling (SEM) method with a Partial Least Squares (PLS) approach. The results of the study indicate that WS has a significant positive effect on OCB-CH, WS has a significant positive effect on PE, PE has a significant positive effect on OCB-CH, and WS, through PE, has a significant positive effect on enhancing OCB-CH.